Movements of the Mandible and Temporomandibular Joint during Jaw Opening and Closing - Robert Hinton; Bob Hutchins; Gerald Hill (Association of American Medical Colleges, 2011)
Abstract Because of their complexity, the movements of the mandible during chewing and those of the temporomandibular joint (TMJ) are typically difficult for students to visualize. This module contains animations that were created to aid dental and medical students at the Baylor College of Dentistry in the visualization of the components of these movements that are the most challenging: the movements of the mandible in the frontal (coronal) plane and the movements of the TMJ and its intraarticular structures in the sagittal plane. The aim was to portray the complex movements in a more understandable way than static positional drawings could. The mandible animation illustrates the typical movement path followed during the opening and closing movements of unilateral mastication. The animation can be stopped at three different points during the movement envelope: following full opening, following closing to approximate the teeth, and just prior to the power stroke. The animations are paired with a PowerPoint that highlights the muscles that are active during the opening and closing phases. This juxtaposition helps to emphasize the phasic yet synergistic contributions of the numerous muscles that produce these complex movements. The temporomandibular joint animation illustrates the movement of the mandibular condyle, the articular disc, and the retrodiscal pad (posterior attachment) during opening and closing movements of the lower jaw. The TMJ animation permits instructors to highlight the differential movements of the intraarticular structures and to discuss factors that affect these movements. Student feedback indicated that the animations significantly aid comprehension of how mastication is effected and how the disc moves relative to the condyle.